İmportance of privacy to prevent sexual abuse of children - (:unkn) unknown (My University, 2012)
Dünyanın en ciddi problemlerinden birisi çocuk sorunlarıdır. Bunların arasında çocukların cinsel istismarı önemli bir yer tutmaktadır. Bu istismarı önleyebilme adına İslâm'ın öngördüğü bir tedbir vardır. O da ailede mahremiyet eğitimidir. Makale, mahremiyetin kaynağı ve eğitimi ile ilgili olup cinsel istismarı önlemede en önemli tedbirlerden birisi olduğunu ortaya koymaktadır.

One of the most important issues in the world is children's problems. Among these child-related issues, sexual abuse of children occupies a central part of their problem. To prevent such abuses, Islam proposes a vital safety measure, which is privacy (Mahremiyet) education in family. This paper sets forth that the source of privacy (and its education) is one of the most effective safeguards in preventing sexual abuse of children, especially within families.
Çoçukların cinsel istismarını önlemede mahremiyetin önemi